FAKTOR-FAKTOR YANG MEMPENGARUHI IHSG PADA PERUSAHAAN PERBANKAN TAHUN 2015-2019 - Mondra Neldi; Nurul Syahira; Elfiswandi Elfiswandi; Zefriyenni Zefriyenni; Fitri Yeni (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2020)
The research aims to determine the effect of the inflation rate, exchange rate,interest rate, and trading volume on the Composite Stock Price Index. Sampling using the Purposive Sampling method acquired 26 companies. The analysis method used is multiple linear regression analysis using SPSS. The results of partial study (Uji-t) show that the inflation rate, exchange rate, and interest rate have a significant effect on the Composite Stock Price Index, while trading volume has no significant effect. The F test results jointly the inflation rate, exchange rate, interest rate, and trading volume have a significant effect on the Composite Stock Price Index. The coefficient of determination (R2) test result also shows that the inflation rate, exchange rate, interest rate, and trading volume have a significant effect on the Composite Stock Price Index of 0,400 or 40,0% while the remaining 60,0% is influenced by other variables outside of this study.